187k views
25 votes
I have to turn this in by tonight

I have to turn this in by tonight-example-1

1 Answer

3 votes

Answer:

x = -11

Explanation:

Convert fraction into negative exponential form:
(36^-^1)^x^-^4=(216^-^1)^x^+^1\\

Simplify using exponent power rule:
(a^n)^m=a^n^m:36^-^x^+^4=216^-^x^-^1

Convert both sides of the equation into terms with same base:
(6^2)^-^x^+^4=(6^3)^-^x^-^1

Simplify using exponent power rule:


(a^n)^m=a^n^m:6^-^2^x^+^8=6^-^3^x^-^3

Based on the given conditions, corresponding exponents are equal:


-2x=8=-3x-3

Rearrange unknown terms to the left side of the equation:


-2x+3x=-3-8

Combine like terms:
x=-3-8

Calculate the sum or difference:
x = -11

Thurs, x = -11

[RevyBreeze]

User TheEpsilon
by
4.8k points